Infrastructuring Telehealth in (In)Formal Patient-Doctor Contexts - Bhat, Karthik S; Jain, Mohit; Kumar, Neha (CSCW 2021, 2021)
Telehealth technologies have long remained on the peripheries of healthcare systems that prioritize in-person healthcare provision. The spread of the COVID-19 pandemic has foregrounded the need to formalize telehealth infrastructures, particularly teleconsultations, to ensure continued care provision through remote mechanisms. In the Indian healthcare context, prior to the pandemic, teleconsultations have been used to substitute for in-person consultations when possible, and to facilitate remote follow-up care without exacerbating pressures on limited personal resources. We conducted a survey and interview study to investigate doctors' and patients' perceptions, experiences, and expectations around teleconsultations, and how these contribute towards supplementing healthcare infrastructures in India, focusing on the changes brought about by the COVID-19 pandemic. In this paper, we describe the efforts of our participants towards infrastructuring telehealth, examining how technologies were adapted to support teleconsultation, how expectations shifted, and how the dynamics of caregiving evolved through this transition. We present implications for the future design and uptake of telehealth, arguing that COVID-19's impact on teleconsultations lays the foundation for new telehealth infrastructures for more inclusive and equitable care.